Evaluation of titanium alloy as heat absorber for solar-based water treatment system - Nattadon Pannucharoenwong (Elsevier, 2021)
Due to the current status of water treatment system it is very difficult to produce fresh clean water without electricity. This research evaluated the intervention of titanium as heat absorber in the heat transfer analysis regarding the solar-based desalination system. The experiment was carried out in a double-slanted distillation unit designed to harness sunlight’s energy. The distillation unit contain a transparent glass shield, contaminated water inlet, treated water outlet, two treatment levels, heat absorber and insulator. Parameters monitors during the experiments included water treatment efficiency, productivity, distillation temperature and distillation rate. Variable included the heat absorber’s surface area with respect to the surface area of water in the chamber (10 to 90%). Experimental results were used to calculate water treatment efficiency using the Engineering Equation Solver (EES), which varied disproportionally with the size of Titanium heat absorber. The highest productivity was observed at 1.61 liter per day with a water treatment efficiency of 26.2%. The payback period of the solar-based distillation prototype was 5.5 years. The fastest distillation rate was monitored at 15:00 on average. Water’s level in distillation chamber and thermal conductivity of the insulator’s thermal conductivity inside both lower and higher still inside the unit have undesirable impact on performance. Wind speed promoted better heat transfer which resulted in an increase in distillation rate. Two numerical equations were developed for calculating distillation efficiency and productivity from input parameters such as operating time and heat absorber’s size. The prototype distillation unit demonstrated excellent results for converting salt water into fresh water.